(untitled) (Journal on Geoinformatics, Nepal, 2025)
Geodetic reference frame is fundamental geodetic infrastructure required for positioning for surveying and mapping purposes. This paper presents a method to develop national level geodetic reference frame tied to global reference frame by utilizing the long-term GNSS observations. The key to realize a national reference frame is to transform Earth-Centered Earth-Fixed (ECEF) X, Y, and Z coordinates from International Terrestrial Reference Frame (ITRF) to national reference frame is by application of 14-Helmert transformation parameters. Initially, precise point positioning (PPP) provides the X, Y, and Z coordinates of reference stations with respect to ITRF, which in turn transformed to national geodetic reference frame. This paper discusses the development of 14-Helmert transformation parameter taking example of Nepal geodetic reference frame being built in near future.